Decrease Expression of E-cadherin in Oral Lichen Planus- A Marker of Premalignant Lesion - Rauf, Manal (International Journal of Pathology, 2022)
Introduction: Lichen planus is a T cell mediated disease with an unknown etiology. It has inflammation of the dermal-epidermal junction having high chances of progressing into squamous cell carcinoma. E-cadherin is responsible for maintaining cell stability and polarity and is down regulated in Lichen plannus. Objective: Objective of the study is to determine the expression of E-cadherin in oral mucosal biopsies as a diagnostic aid for evaluation of malignant potential of oral lichen planus. Materials: 52 samples of lichen planus were collected of clinically diagnosed patients from January to December 2019 in the Department of Histopathology, Pakistan Institute of Medical Sciences (PIMS), Shaheed Zulfiqar Ali Bhutto Medical University (SZABMU), Islamabad. 16 cases comprising of normal unremarkable oral mucosa were included in control group. Result: Of the total 16 specimens of normal oral mucosa, all the cases i.e. 100 % showed diffuse homogenous positivity with E-cadherin .On the other hand, all of the 52 cases of OLP showed heterogeneous pattern of staining with E cadherin, out of which, 25 cases (48%) showed 3+ score with E-cadherin, 15 cases (28.8%) showed 4+ score and 12 cases (23%) showed 2+ score. Conclusion: E-cadherin showed diffuse homogeneous staining with normal mucosa and partial heterogeneous pattern on Lichen planus, showing that E-cadherin may play a significant role as a marker of malignant potential of lichen planus.